Solidarity at Issue: Pandemics and Religious Belief - Giddy, John Patrick (Phronimon, 2021)
A global pandemic such as that of the 2020 Covid-19 corona virus, causing great suffering and loss of life, brings home the difficult conditions that make for our fragile human life. But the question that religious belief poses, about “natural evil” in a world created by a loving God, satirised by Voltaire in the 18th century, masks the more existential problem, the possibility of greater human solidarity. In the background is the Deist view of God complementing the “polite society” of mutual benefit and guaranteeing the latter’s benevolent outcome. It is a worldview, as Charles Taylor (2007) explains, that has put aside the premodern idea of human transformation, that was symbolised by religious virtuosi, saints, theophanies, and so on, now looked upon with suspicion by modernity. But the possibility of transformation, of a generous human response to suffering, is what is called for in a pandemic. In Camus’ novel, The Plague, we see the more authentic response that resists being boxed in by religious enthusiasts to a constricted and ideological affirmation of a cosmic picture that obscures the fault-lines of bourgeois society.